GPON-Based FTTH Network Design in Koto Gunung Village - Iqbal Rizantha; Aprinal Adila Asril; Sahid Ridho (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid development of information and communication technology has increased the demand for fast and reliable internet access, especially in rural areas. However, Koto Gunung Village, Batang Kapas District, Pesisir Selatan Regency, still experiences limited and unstable internet connectivity. Therefore, this research aims to design a Fiber To The Home (FTTH) network based on Gigabit Passive Optical Network (GPON) technology to provide stable and high-quality internet services for the community. The research method used in this study is the Network Development Life Cycle (NDLC), which includes literature study, field survey, network route design using Google Earth Pro and AutoCAD, and network simulation using OptiSystem software. The network performance was analyzed based on attenuation, link power budget, rise time budget, and Bit Error Rate (BER) parameters. The results showed that the total attenuation values for distribution route 1 and route 2 were 23.8216 dB and 23.874 dB, respectively, which are still below the maximum allowable standard of 28 dB. The total rise time values obtained were 0.2636 ns and 0.264 ns, which also meet the maximum standard of 0.29 ns. In addition, the simulation results showed BER values of 1.42 × 10⁻¹⁹ and 2.322 × 10⁻¹⁹, indicating excellent transmission quality with very low error rates. Based on these results, the designed GPON-based FTTH network is considered feasible for implementation in Koto Gunung Village.